Preparation process of polylactic acid with high heat resistance
The chemical graft crosslinking of microcrystalline cellulose modified with polylactic acid is solved by grafting long-chain alkane modified microcrystalline cellulose and polylactic acid, which is solved by poor heat resistance and significantly improves its heat resistance and mechanical properties, and is suitable for high-temperature applications while maintaining the The green and environmentally friendly properties of the material.
Patent Information
- Application Number
- CN202411699387.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-13
- Filing Date
- 2024-11-26
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polylactic acid has a slow crystallization rate and low crystallinity, which leads to poor heat resistance, which limits its application in the fields of stretchless injection molding and film production. The existing nucleating agents affect transparency and mechanical properties and are non-degradable nucleating. The agent is harmful to the environment.
Use grafted long-chain alkane-modified microcrystalline cellulose to react with carboxylic acid groups on the surface of polylactic acid to form chemical graft crosslinking, improve the heat resistance and mechanical properties of polylactic acid, and utilize the rigidity and longness of microcrystalline cellulose. The flexibility of chain aliphatic hydrocarbons enhances the interface bonding and network structure of polylactic acid.
It significantly improves the heat resistance and mechanical properties of polylactic acid, delays thermal decomposition, enhances the tensile performance and dimensional stability of the material, making it suitable for high-temperature applications, while maintaining the green, environmentally friendly and degradable properties of the material.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polylactic acid, in particular to a preparation process of highly heat-resistant polylactic acid. Background Art
[0002] Polylactic acid is an emerging green recyclable material. Due to its excellent biodegradability, biocompatibility, and high strength and high modulus mechanical properties, it has attracted the attention of many scholars. It is a recognized environmentally friendly material. However, due to its inherent structure, polylactic acid also has some defects. Due to its slow crystallization rate and low crystallinity, polylactic acid molding has disadvantages such as long cycle and poor dimensional stability. Therefore, it is subject to many restrictions in the field of non-stretching injection molding and film production. In addition, due to the low crystallinity of polylactic acid, its heat resistance temperature is only 60°C. It is easy to thermally degrade and break the molecular chain during high-temperature shearing, which limits the application of polylactic acid. Therefore, improving the heat resistance of polylactic acid is very important to broaden the application range of polylactic acid.
[0003] At present, the patents for modifying the heat resistance of polylactic acid mainly use methods such as adding nucleating agents and filling to improve the heat resistance. The existing nucleating agents are mainly divided into two categories, namely inorganic nucleating agents and organic nucleating agents, mainly including montmorillonite, talc, titanium dioxide, etc. These nucleating agents have poor compatibility with polylactic acid, and there are problems of agglomeration and uneven dispersion in the polymer. When the addition amount is high, it will affect the transparency and mechanical properties of the polylactic acid material; Chinese patent CN101423625B uses a phosphorus compound metal salt with a reducing effect as a nucleating agent for the rapid crystallization of polylactic acid resin. While promoting the growth of crystals and refining the crystal size, the crystallization nucleating agent has strong antioxidant, heat resistance, and hydrolysis resistance, but there is a problem of being non-degradable and harmful to the environment.
[0004] Chinese patent CN101602884B discloses a method for improving the heat resistance of polylactic acid by blending polylactic acid with starch and using a nucleating agent to improve crystallinity. The method solves the technical problems of poor biodegradability, high cost and poor mechanical properties of products in existing methods for preparing polylactic acid cross-linked materials and polymer cross-linked materials. However, the polylactic acid prepared by the method has general heat resistance and poor transparency. Chinese patent CN101157793B discloses a heat-resistant polylactic acid blend and a preparation method thereof, which solves the problems of poor heat resistance and weak mechanical properties of existing heat-resistant polylactic acid blends. However, the polylactic acid blended by the technology is amorphous polylactic acid, so the improvement of heat resistance is limited. On this basis, the present invention utilizes microcrystalline cellulose modified by grafting long-chain alkanes, which has the characteristics of flexibility of long-chain aliphatic hydrocarbons and rigidity and high heat resistance of cellulose, and then reacts with the carboxylic acid groups on the surface of polylactic acid to form a strong interface bond. The prepared polylactic acid has high heat resistance, excellent mechanical properties and is green, environmentally friendly and degradable. Summary of the invention
[0005] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides a preparation process of polylactic acid with high heat resistance, which solves the problem of poor heat resistance of polylactic acid.
[0006] (II) Technical solution A preparation process of highly heat-resistant polylactic acid, the preparation process of highly heat-resistant polylactic acid is carried out according to the following steps: (1) Add 100 parts of crushed microcrystalline cellulose to an aqueous solution of 30-40 parts of sodium hydroxide and 44-50 parts of urea, stir rapidly for 5-15 minutes to obtain a gel slurry, then add 2-5L of deionized water and stir, filter, wash with deionized water until neutral, and dry to obtain alkalized microcrystalline cellulose.
[0007] (2) Add lithium chloride to N'N-dimethylacetamide solvent, stir and dissolve at 50-70°C under nitrogen atmosphere, then add alkalized microcrystalline cellulose, stir and swell, add undecylenic acid chloride and pyridine. After the reaction is completed, pour the reaction solution into methanol, filter, wash with deionized water and anhydrous ethanol in turn, and dry to obtain alkyl olefin modified cellulose.
[0008] (3) Add 100 parts of alkyl olefin-modified cellulose to deionized water and acetone solvent, stir and soak, add 0.1-0.4 parts of initiator dibenzoyl peroxide under nitrogen atmosphere, stir evenly and then add 5-30 parts of glycidyl methacrylate. After the reaction is completed, filter and wash with deionized water and acetone in turn. Perform Soxhlet extraction of the filter cake with acetone for 24-48 hours to obtain epoxyalkane-modified cellulose.
[0009] (4) Add polylactic acid to toluene solvent, stir to swell, add tetrabutylammonium bromide and epoxyalkane to modify cellulose under nitrogen atmosphere, add methanol to precipitate after the reaction, filter, and wash with ethanol to obtain highly heat-resistant polylactic acid.
[0010] Preferably, in step (2), the reactants are, by weight, 100 parts of microcrystalline cellulose, 300-400 parts of lithium chloride, 120-330 parts of undecylenic chloride, and 3-8 parts of pyridine.
[0011] Preferably, in step (2), the reaction temperature is 90-120° C. and the reaction time is 12-24 h.
[0012] Preferably, the volume ratio of deionized water to acetone solvent in step (3) is (1-2):1.
[0013] Preferably, in step (3), the reaction temperature is 70-100° C. and the reaction time is 3-6 h.
[0014] Preferably, in step (4), the reactants are calculated by weight as follows: 100 parts of polylactic acid, 0.65-1.12 parts of tetrabutylammonium bromide, and 25-55 parts of epoxyalkane-modified cellulose.
[0015] Preferably, in step (4), the reaction temperature is 110-140° C. and the reaction time is 6-12 h.
[0016] 3. Beneficial technical effects The invention first activates microcrystalline cellulose under sodium hydroxide conditions to obtain alkalized cellulose, then esterifies the cellulose with undecylenyl chloride under the catalysis of pyridine to obtain alkyl olefin modified cellulose, and polymerizes the introduced olefin group with glycidyl methacrylate to obtain epoxy alkane modified cellulose. Finally, the cellulose reacts with the carboxyl group of polylactic acid under the catalysis of tetrabutylammonium bromide and the epoxy group of epoxy alkane modified cellulose to achieve chemical grafting and crosslinking of polylactic acid and alkane modified cellulose to obtain high heat resistant polylactic acid.
[0017] The present invention takes advantage of the good compatibility of modified cellulose prepared by microcrystalline cellulose and long-chain alkyl olefin with a polylactic acid matrix. The pulling out of longer fibers is beneficial to the mechanical properties of polylactic acid, and the obtained chain segments have both the flexibility of long-chain fatty hydrocarbons and the rigidity of cellulose. The fibers, as high-rigidity materials, exist as reinforcements in the polylactic acid matrix, play a "skeleton" role, and give the polylactic acid excellent rigidity. In addition, the modified cellulose can effectively absorb and transmit forces, improve the crystallinity of polylactic acid, and enhance the mechanical properties of polylactic acid. Polylactic acid and alkane-modified cellulose form chemical grafting and cross-linking, which strengthens the interaction between molecular chains, increases the interface bonding with polylactic acid, increases the density of the network structure between polylactic acid and cellulose, delays the thermal decomposition of polylactic acid, and significantly improves the tensile properties and heat resistance of polylactic acid. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Preparation of undecylenic acid chloride: add 1 mol of undecylenic acid to dichloromethane solvent, stir to dissolve, add 1.2 mol of thionyl chloride and 4-6 drops of N'N-dimethylformamide, react at room temperature for 2 hours, and after the reaction is completed, remove the excess thionyl chloride by vacuum distillation to obtain undecylenic acid chloride. Example 1
[0020] (1) Add 100 parts of crushed microcrystalline cellulose to an aqueous solution of 35 parts of sodium hydroxide and 44 parts of urea, stir rapidly for 15 minutes to obtain a gel slurry, then add 3 L of deionized water and stir, filter, wash with deionized water until neutral, and dry to obtain alkalized microcrystalline cellulose.
[0021] (2) Add 90 parts of lithium chloride to N'N-dimethylacetamide solvent, stir and dissolve at 60°C under a nitrogen atmosphere, then add 26 parts of alkalized microcrystalline cellulose, stir and swell, add 33 parts of undecylenic acid chloride and 2 parts of pyridine, react at 100°C for 15 hours, pour the reaction solution into methanol, filter, wash with deionized water and anhydrous ethanol in turn, and dry to obtain alkyl olefin modified cellulose.
[0022] (3) Add 30 parts of alkyl olefin-modified cellulose to a deionized water and acetone solvent in a volume ratio of 2:1, stir and soak, add 0.12 parts of initiator dibenzoyl peroxide under a nitrogen atmosphere, stir evenly and then add 6 parts of glycidyl methacrylate, react at 70°C for 5 hours, filter, wash with deionized water and acetone in turn, and perform Soxhlet extraction of the filter cake with acetone for 30 hours to obtain epoxyalkane-modified cellulose.
[0023] (4) Add 50 parts of polylactic acid to toluene solvent, stir and swell, add 0.42 parts of tetrabutylammonium bromide and 13 parts of epoxyalkane-modified cellulose under nitrogen atmosphere, react at 120°C for 6 hours, add methanol for precipitation, filter, and wash with ethanol to obtain highly heat-resistant polylactic acid. Example 2
[0024] (1) Add 48 parts of crushed microcrystalline cellulose to an aqueous solution of 15 parts of sodium hydroxide and 23 parts of urea, stir rapidly for 15 minutes to obtain a gel slurry, then add 3 L of deionized water and stir, filter, wash with deionized water until neutral, and dry to obtain alkalized microcrystalline cellulose.
[0025] (2) Add 50 parts of lithium chloride to N'N-dimethylacetamide solvent, stir and dissolve at 70°C under nitrogen atmosphere, then add 18 parts of alkalized microcrystalline cellulose, stir and swell, add 42 parts of undecylenic acid chloride and 1.2 parts of pyridine, react at 90°C for 14 hours, pour the reaction solution into methanol, filter, wash with deionized water and anhydrous ethanol in turn, and dry to obtain alkyl olefin modified cellulose.
[0026] (3) Add 100 parts of alkyl olefin modified cellulose to a deionized water and acetone solvent in a volume ratio of 1:1, stir and soak, add 0.3 parts of initiator dibenzoyl peroxide under a nitrogen atmosphere, stir evenly and then add 20 parts of glycidyl methacrylate, react at 90°C for 4 hours, filter, wash with deionized water and acetone in turn, and perform Soxhlet extraction of the filter cake with acetone for 48 hours to obtain epoxyalkane modified cellulose.
[0027] (4) Add 50 parts of polylactic acid to toluene solvent and stir to swell. Add 0.61 parts of tetrabutylammonium bromide and 18 parts of epoxyalkane-modified cellulose under nitrogen atmosphere. After reacting at 130°C for 7 hours, add methanol for precipitation, filter, and wash with ethanol to obtain highly heat-resistant polylactic acid. Example 3
[0028] (1) Add 80 parts of crushed microcrystalline cellulose to an aqueous solution of 24 parts of sodium hydroxide and 37 parts of urea, stir rapidly for 10 minutes to obtain a gel slurry, then add 4 L of deionized water and stir, filter, wash with deionized water until neutral, and dry to obtain alkalized microcrystalline cellulose.
[0029] (2) Add 150 parts of lithium chloride to N'N-dimethylacetamide solvent, stir and dissolve at 70°C under a nitrogen atmosphere, then add 60 parts of alkalized microcrystalline cellulose, stir and swell, add 110 parts of undecylenic acid chloride and 5 parts of pyridine, react at 120°C for 18 hours, pour the reaction solution into methanol, filter, wash with deionized water and anhydrous ethanol in turn, and dry to obtain alkyl olefin modified cellulose.
[0030] (3) Add 40 parts of alkyl olefin-modified cellulose to a deionized water and acetone solvent in a volume ratio of 2:1, stir and soak, add 0.15 parts of initiator dibenzoyl peroxide under a nitrogen atmosphere, stir evenly and then add 10 parts of glycidyl methacrylate, react at 70°C for 6 hours, filter, wash with deionized water and acetone in turn, and perform Soxhlet extraction of the filter cake with acetone for 42 hours to obtain epoxyalkane-modified cellulose.
[0031] (4) Add 50 parts of polylactic acid to toluene solvent, stir and swell, add 0.58 parts of tetrabutylammonium bromide and 2,2-epoxyalkane-modified cellulose under nitrogen atmosphere, react at 140°C for 6 hours, add methanol for precipitation, filter, and wash with ethanol to obtain highly heat-resistant polylactic acid. Example 4
[0032] (1) Add 30 parts of crushed microcrystalline cellulose to an aqueous solution of 12 parts of sodium hydroxide and 15 parts of urea, stir rapidly for 15 minutes to obtain a gel slurry, then add 2 L of deionized water and stir, filter, wash with deionized water until neutral, and dry to obtain alkalized microcrystalline cellulose.
[0033] (2) Add 40 parts of lithium chloride to N'N-dimethylacetamide solvent, stir and dissolve at 60°C under nitrogen atmosphere, then add 12 parts of alkalized microcrystalline cellulose, stir and swell, add 33 parts of undecylenic acid chloride and 0.8 parts of pyridine, react at 110°C for 20 hours, pour the reaction solution into methanol, filter, wash with deionized water and anhydrous ethanol in turn, and dry to obtain alkyl olefin modified cellulose.
[0034] (3) Add 60 parts of alkyl olefin-modified cellulose to a deionized water and acetone solvent in a volume ratio of 2:1, stir and soak, add 0.28 parts of initiator dibenzoyl peroxide under a nitrogen atmosphere, stir evenly and then add 15 parts of glycidyl methacrylate, react at 100°C for 5 hours, filter, wash with deionized water and acetone in turn, and perform Soxhlet extraction of the filter cake with acetone for 28 hours to obtain epoxyalkane-modified cellulose.
[0035] (4) Add 50 parts of polylactic acid to toluene solvent, stir and swell, add 0.48 parts of tetrabutylammonium bromide and 27 parts of epoxyalkane-modified cellulose under nitrogen atmosphere, react at 120°C for 12 hours, add methanol for precipitation, filter, and wash with ethanol to obtain highly heat-resistant polylactic acid.
[0036] Comparative Example 1 (1) Add 100 parts of crushed microcrystalline cellulose to an aqueous solution of 40 parts of sodium hydroxide and 50 parts of urea, stir rapidly for 10 minutes to obtain a gel slurry, then add 4 L of deionized water and stir, filter, wash with deionized water until neutral, and dry to obtain alkalized microcrystalline cellulose.
[0037] (2) Add 50 parts of polylactic acid to toluene solvent and stir to swell. Add 0.52 parts of tetrabutylammonium bromide and 27 parts of alkalized microcrystalline cellulose under nitrogen atmosphere. After reacting at 140°C for 10 hours, add methanol for precipitation, filter, and wash with ethanol to obtain a polylactic acid / microcrystalline cellulose material.
[0038] Comparative Example 2 (1) Add 100 parts of crushed microcrystalline cellulose to an aqueous solution of 40 parts of sodium hydroxide and 48 parts of urea, stir rapidly for 15 minutes to obtain a gel slurry, then add 5 L of deionized water and stir, filter, wash with deionized water until neutral, and dry to obtain alkalized microcrystalline cellulose.
[0039] (2) Add 40 parts of lithium chloride to N'N-dimethylacetamide solvent, stir and dissolve at 60°C under nitrogen atmosphere, then add 12 parts of alkalized microcrystalline cellulose, stir and swell, add 33 parts of undecylenic acid chloride and 0.8 parts of pyridine, react at 110°C for 22 hours, pour the reaction solution into methanol, filter, wash with deionized water and anhydrous ethanol in turn, and dry to obtain alkyl olefin modified cellulose.
[0040] (3) Add 50 parts of polylactic acid to toluene solvent and stir to swell. Add 0.58 parts of tetrabutylammonium bromide and 27 parts of alkyl olefin-modified cellulose under nitrogen atmosphere. After reacting at 110°C for 15 hours, add methanol for precipitation, filter, and wash with ethanol to obtain a polylactic acid / alkyl olefin cellulose material.
[0041] Mechanical properties test: The tensile properties were tested according to standard GB / T1447-2005, using a WDW3100 micro-controlled electronic universal testing machine to prepare test specimens of 20mm×5mm×3mm. The tensile rate was 10mm / min, and the test was repeated 5 times to obtain the average value.
[0042]
[0043] The above table compares the tensile properties and Young's modulus of each embodiment and the comparative example. As the content of modified epoxyalkane-modified cellulose increases, the tensile strength of polylactic acid increases accordingly. In Example 3, when the content of modified cellulose reaches 30%, the tensile strength of polylactic acid reaches the maximum value (53.8MPa), which is 123% higher than the alkalized cellulose material in Comparative Example 1. This is because when subjected to tension, the fiber, as a high-rigidity material, exists as a reinforcement in the polylactic acid matrix, plays a "skeleton" role, mainly bearing external forces and transmitting forces, showing enhanced mechanical properties. However, further increasing the content of epoxyalkane-modified cellulose reduces the tensile strength. This may be because when too much cellulose is stretched by external forces, the fiber itself becomes shorter, and these short fibers have a negative impact on the mechanical properties of polylactic acid. In addition, too much cellulose will also make the fluidity of the processing process worse, and some fibers will entangle and agglomerate. Stress concentration occurs inside the material, which is easy to cause cracks to form, thereby affecting the tensile strength of polylactic acid.
[0044] In the above table, the Young's modulus also shows a trend of slowing down with the increase of the content of epoxyalkane-modified cellulose. Example 4 is 120% higher than that in Comparative Example 2. This is because the high-strength and high-modulus cellulose has good compatibility with the polylactic acid matrix, forming chemical grafting and cross-linking, which strengthens the interaction between the molecular chains and improves the rigidity of the polylactic acid. Macroscopically, it is manifested as an increase in Young's modulus. Although Comparative Example 2 contains long-chain aliphatic hydrocarbon cellulose but does not have flexible epoxy groups, the Young's modulus is lower than that of Example 1, but still higher than that of Comparative Example 1, indicating that the long-chain aliphatic hydrocarbon has a certain flexibility.
[0045] Vicat softening temperature test: According to GB / T1633-2000, the Vicat softening temperature of the material is tested using a SWB-300C / D thermal deformation Vicat softening point thermometer. The test load is 1 kg and the temperature rise is 3°C / min.
[0046]
[0047] It can be seen from the above table that with the increase of the content of epoxyalkane-modified cellulose, the Vicat softening temperature of polylactic acid shows a trend of first increasing and then decreasing. When the content of epoxyalkane-modified cellulose in Example 3 is 30%, the Vicat softening temperature at this time reaches 166.1°C, which is 50% higher than the polylactic acid / microcrystalline cellulose in Comparative Example 1. This shows that the increase in the content of epoxyalkane-modified cellulose can significantly improve the heat deformation resistance of polylactic acid, and the better the dimensional stability of the material when heated, the prepared polylactic acid has high heat resistance.
[0048] Differential scanning calorimetry test: MDSC2920 scanning calorimeter was used to conduct thermal analysis of polylactic acid in a nitrogen atmosphere, with a heating rate of 10°C / min, a sample mass of 5-8mg, and a test temperature range of 30-210°C.
[0049]
[0050] Generally speaking, the higher the glass transition temperature, the better the stability of the material and the stronger the deformation resistance. It can be seen from the above table that as the content of epoxyalkane-modified cellulose increases, the glass ring transition temperature of polylactic acid first increases and then slows down. The content of epoxyalkane-modified cellulose in Example 3 is 30%. Compared with the material in which only alkalized cellulose is added in Comparative Example 1, Tg is increased by 16%. This is because the addition of epoxyalkane-modified cellulose limits and restrains the movement and diffusion of polylactic acid molecular segments during the glass transition process, thereby increasing the glass transition temperature. In addition, the reason for the slow growth of Tg is that an appropriate amount of epoxyalkane-modified cellulose can promote the formation of imperfect polylactic acid crystals and play a role in heterogeneous nucleation, thereby helping to form a crystal nucleus with a higher degree of perfection and improve the crystallinity of polylactic acid. Therefore, the molecular chain will consume more energy under the action of heat, resulting in an increase in the thermal decomposition temperature, thereby enhancing the heat resistance of polylactic acid.
[0051] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A process for preparing highly heat-resistant polylactic acid, characterized in that: The preparation process is carried out according to the following steps: (1) Add 100 parts of crushed microcrystalline cellulose to an aqueous solution of 30-40 parts of sodium hydroxide and 44-50 parts of urea, stir rapidly for 5-15 minutes to obtain a gel slurry, then add 2-5L of deionized water and stir, filter, wash with deionized water until neutral, and dry to obtain alkalized microcrystalline cellulose; (2) adding lithium chloride to N'N-dimethylacetamide solvent, stirring and dissolving at 50-70°C under nitrogen atmosphere, adding alkalinized microcrystalline cellulose, stirring and swelling, adding undecylenic acid chloride and pyridine, and after the reaction is completed, pouring the reaction solution into methanol, filtering, washing with deionized water and anhydrous ethanol in turn, and drying to obtain alkyl olefin modified cellulose; (3) Add 100 parts of alkyl olefin-modified cellulose to deionized water and acetone solvent, stir and soak, add 0.1-0.4 parts of initiator dibenzoyl peroxide under nitrogen atmosphere, stir evenly and then add 5-30 parts of glycidyl methacrylate. After the reaction is completed, filter, wash with deionized water and acetone in turn, and perform Soxhlet extraction of the filter cake with acetone for 24-48 hours to obtain epoxyalkane-modified cellulose; (4) adding polylactic acid to toluene solvent, stirring and swelling, adding tetrabutylammonium bromide and epoxyalkane-modified cellulose under nitrogen atmosphere, adding methanol for precipitation after the reaction, filtering, and washing with ethanol to obtain highly heat-resistant polylactic acid; In step (2), the reactants are, by weight, 100 parts of microcrystalline cellulose, 300-400 parts of lithium chloride, 120-330 parts of undecylenic acid chloride, and 3-8 parts of pyridine; In the step (3), the volume ratio of deionized water to acetone solvent is (1-2):1; In the step (4), the reactants are calculated by weight: 100 parts of polylactic acid, 0.65-1.12 parts of tetrabutylammonium bromide, and 25-55 parts of epoxyalkane-modified cellulose.
2. The process for preparing highly heat-resistant polylactic acid according to claim 1, characterized in that: In the step (2), the reaction temperature is 90-120° C. and the reaction time is 12-24 h.
3. The process for preparing highly heat-resistant polylactic acid according to claim 1, characterized in that: In the step (3), the reaction temperature is 70-100° C. and the reaction time is 3-6 h.
4. The process for preparing highly heat-resistant polylactic acid according to claim 1, characterized in that: In the step (4), the reaction temperature is 110-140° C. and the reaction time is 6-12 h.
Citation Information
Patent Citations
Heat-proof polylactic acid blend and preparation method thereof
CN101157793B
Rapid nucleating agent of polylactic resin
CN101423625B
A heat-resistant polylactic acid composite material and its preparation method
CN101602884B